The motivation‐anxiety interface in language learning: A regulatory focus perspective. (18th June 2021) - Jiang, Chen; Papi, Mostafa
Abstract: The study examined the relationship between chronic regulatory focus, L2 self‐guides, L2 anxiety, and motivated behavior. Questionnaire data were collected from 161 English learners in a foreign language context. Multiple regression results showed that the participants' promotion focus (concerned with accomplishments and achievements) strongly and negatively predicted their L2 anxiety whereas their prevention focus (concerned with safety and obligations) was unrelated to L2 anxiety. Additionally, ought L2 self/own and ought L2 self/other, which have a prevention focus, positively predicted L2 anxiety, whereas ideal L2 self/own, which has a promotion focus, was a negative predictor. L2 anxiety was not directly related to motivated behavior for either promotion‐focused or prevention‐focused learners. The results suggest that a promotion‐focused approach in L2 learning and teaching might minimize L2 anxiety. 抽象: 本研究探索了长期调节定向, 二语自我指导, 二语焦虑感, 和动机行为之间的关系。本研究收集了161名英语学习者的调查问卷。多元回归分析结果显示, 本研究的调查对象的促进定向(拥有促进定向的调查对象更关注做事情的相关成就和成果)对其自身的二语焦虑感有显著的负向预测作用, 而本研究的调查对象的预防定向(拥有预防定向的调查对象更关注做事情的相关安全性和义务)与其本身的二语焦虑感没有显著关系。此外, 一方面, 拥有二语应然自我/自我视角和二语应然自我/重要他人视角这两个研究变量的调查对象同时也拥有预防定向, 这两个研究变量对二语焦虑感都有正向预测作用。另一方面, 拥有二语理想自我/自我视角这个研究变量的调查对象同时也拥有促进定向, 这个研究变量对二语焦虑感有负向预测作用。对于无论是拥有促进定向还是拥有预防定向的调查对象, 他们的二语焦虑感和动机行为之间都没有直接关系。该研究的结果表明, 在二语学习和教学中采用促进定向相关的教学方法可以减少二语学习的焦虑感。 关键字 英语作为外语(的教育), 二语焦虑感, 二语学习动机, 调节定向, 二语自我指导